Can sandalwood in East Nusa Tenggara survive?: lessons from the policy impact on resource sustainability - Rohadi, D.; Maryani, R.; Belcher, B.; Ruíz Pérez, M.; Widnyana, M. (2000)
This paper discusses the policy aspects of sandalwood in East Nusa Tenggara province, focusing primarily on the impacts of regional government regulations on the resource sustainability. The paper is based on a field survey that was conducted during July-August 1999, and various publications and official reports from the region